Candidemia Diagnosis With T2 Nuclear Magnetic Resonance in a PICU: A New Approach. Issue 2 (12th October 2020) - Cendejas-Bueno, Emilio; Falces-Romero, Iker; Laplaza-González, María; Escosa-García, Luis; Schuffelmann-Gutierrez, Cristina; Romero-Gómez, María P.; Verdú-Sánchez, Cristina; Calderón-Llopis, Belén; Amores-Hernández, Irene; Pemán, Javier; Gómez-Zamora, Ana; Río-García, Miguel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Early diagnosis of invasive Candida infections is a challenge for pediatricians, intensivists, and microbiologists. To fill this gap, a new nanodiagnostic method has been developed using manual application of T2 nuclear magnetic resonance to detect Candida species. The aim of this study was to evaluate, prospectively, the usefulness as a tool diagnosis of the T2Candida panel in pediatric patients admitted at the PICU compared with blood culture. DESIGN: This is a prospective, observational, and unicentric study to compare T2Candida results with simultaneous blood cultures for candidemia diagnose. SETTING: This study was carried out in a 1, 300-bed tertiary care hospital with a 16-bed medical-surgical PICU. PATIENTS: Sixty-three patients from 0 to 17 years old were enrolled in this study, including those undergoing solid organ transplantation (kidney, liver, pulmonary, multivisceral, intestinal, and heart) and hematopoietic stem cell transplantation. MEASUREMENTS AND MAIN RESULTS: Seven patients were positive by the T2Candida test. Only two of them had the simultaneous positive blood culture. T2Candida yielded more positive results than blood cultures. CONCLUSIONS: T2Candida might be useful for the diagnosis of candidemia in PICUs. The prevalence of candidemia might be underestimated in this pediatric population. The use of this diagnostic tool in these units may help clinicians to start adequate and timely antifungal treatments.